Development of reading skills and motivation in learning English as a function of young learner`s previous language background: Kazakhstani context (Eurasian Journal of Philology Science and Education, 2021)
The article enhances practical effectiveness of English proficiency reading skills among young language learners in Kazakhstan requires the improvement and development of knowledge regarding Educational standard of European framework. Since 2009 when Kazakhstan has started to participate in the Program for International Students Assessment (PISA) low results of Kazakhstani 15-year-old students in the reading literacy (M=390 in 2009 to M=387 in 2018) could be worrying in terms of literacy development and the quality of education (OECD, 2020) because students have not received enough «key knowledge and skills essential for full participation in society» (PISA, 2018). The problem of low performances in reading domain still becomes obvious as reading plays one the pivotal role in the process of academic and intellectual processes of human beings. A brief overview of theoretical frameworks and stages in reading domain are represented and discussed, as well as the factors for motivating and developing reading skills in English as the foreign for young learners are defined. In particular, revealing the gaps and omissions in the system of secondary education in Kazakhstan preventing young learners to be proficient in English as a foreign language (EFL). Thus, the main aim of this study is, generally to investigate the niche of young learners’ lower results in reading literacy, to find out what issues prevent to improve reading level in learning English as well as trying to construct and modify the framework for further English proficiency reading skills in the context of Kazakhstan.